2002
DOI: 10.1523/jneurosci.22-10-03898.2002
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor-β1 Increases Bad Phosphorylation and Protects Neurons Against Damage

Abstract: Despite the characterization of neuroprotection by transforming growth factor-beta1 (TGF-beta1), the signaling pathway mediating its protective effect is unclear. Bad is a proapoptotic member of the Bcl-2 family and is inactivated on phosphorylation via mitogen-activated protein kinase (MAPK). This study attempted to address whether MAPK signaling and Bad phosphorylation were influenced by TGF-beta1 and, furthermore, whether these two events were involved in the antiapoptotic effect of TGF-beta1. We found a gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
178
1
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(185 citation statements)
references
References 56 publications
5
178
1
1
Order By: Relevance
“…Unexpectedly, activated TGF-b attenuated HUVEC apoptosis. Although this observation is in line with several reports on the protective effect of TGF-b against apoptosis of cells other than HUVECs, 40,[49][50][51][52][53] our observations are not in complete accordance with the findings on the apoptosis-inducing effect of recombinant TGFb1 on bovine capillary endothelial cells. 5 While attempting to reproduce those findings, we observed that HUVECs were markedly resistant to TGF-b1-induced apoptosis (results not shown), consistent with observations by others.…”
Section: Discussioncontrasting
confidence: 59%
“…Unexpectedly, activated TGF-b attenuated HUVEC apoptosis. Although this observation is in line with several reports on the protective effect of TGF-b against apoptosis of cells other than HUVECs, 40,[49][50][51][52][53] our observations are not in complete accordance with the findings on the apoptosis-inducing effect of recombinant TGFb1 on bovine capillary endothelial cells. 5 While attempting to reproduce those findings, we observed that HUVECs were markedly resistant to TGF-b1-induced apoptosis (results not shown), consistent with observations by others.…”
Section: Discussioncontrasting
confidence: 59%
“…TGF-β1 administered into the brain reduced the infarct size dose dependently in experimental models of ischemia including permanent occlusion of the left middle cerebral artery by microbipolar electrocoagulation in mice (Prehn et al, 1993), autologous clot embolus injection into the right internal carotid artery in rabbit (Gross et al, 1993), and transient middle cerebral artery occlusion in rat (Zhu et al, 2002). In turn, antagonizing the endogenous action of TGF-β1 with a soluble TGF-β type II receptor resulted in a dramatic increase in infarct area (Ruocco et al, 1999).…”
Section: Neuroprotective Function In Brain Ischemiamentioning
confidence: 99%
“…Treatment with another PI3K inhibitor, wortmannin (100 nM) (Powis et al, 1994), also prevented the NT-3-induced increase in SSC frequency (data not shown). In contrast, inhibition of MAP kinase pathway by either 2Ј-amino-3Ј-methoxyflavone (PD098059) (10 M) (Alessi et al, 1995) or 1,4-diamino-2,3-dicyano-1,4-bis(2-aminophenylthio)butadiene (U0126) (10 M) (Zhu et al, 2002) did not abolish the NT-3-induced increase in SSC frequency (U0126, 5.3 Ϯ 0.6 events/min; PD098059, 5.2 Ϯ 7.8 events/min; U0126 with NT-3, 13.1 Ϯ 1.6 events/min; PD098059 with NT-3, 14.6 Ϯ 1.0) (Fig. 5A).…”
Section: Critical Role Of Akt In Nt-3-mediated Long-term Synaptic Effmentioning
confidence: 99%